Kekentalan Darah Tikus Putih (Rattus norvegicus) Strain Wistar Bunting yang Mengkonsumsi MSG Organik dan Sintetis Dosis 60-120 mg/kg - Ulya Ananda Putri Febrianti (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to determine blood viscosity in pregnant Wistar strain rats given organic MSG and synthetic MSG with dose treatment. This research is a descriptive quantitative study using an experimental method and a Completely Randomized Design (CRD) consisting of 4 treatments with 3 replications each. Groups P1 and P2 were given organic MSG, while groups P4 and P5 were given synthetic MSG. The obtained data were statistically analyzed using One-Way Analysis of Variance (ANOVA) with SPSS version 20, followed by the DMRT (Duncan’s Multiple Range Test). The results showed that the P1 group with organic MSG had an average blood clotting time of 16.39 minutes, P2 was 14.39 minutes, P4 with synthetic MSG was 7.87 minutes, and P5 was 9.33 minutes. In conclusion, the blood viscosity of pregnant Wistar strain white rats (Rattus norvegicus) after being treated with organic and synthetic MSG shows that the consumption of both types of MSG can reduce blood viscosity levels, as evidenced by the slowing of blood clotting time. The effective dose of organic and synthetic MSG consumption is 120 mg/kg. Keywords: Blood Viscosity, Pregnancy, Organic MSG, Synthetic MSG, Wistar Strain Rats